SISTEM SYARIAH, RISIKO DAN PROFITABILITAS BANK UMUM SWASTA NASIONAL DEVISA DI INDONESIA - al-Chaq, Achmad Mujaahid (Economic Faculty, Attahiriyah Islamic University, 2017)
This research have a purpose to knowing first relationship between credit risk, liquidity risk, operation risk, market risk and capital adequacy to profitability, second to analyst that a syariah priciple able to reduce impact of risk to profitability. This research taken in Bank Umum Swasta Nasional Devisa Indonesia, with using panel regression method in Eviews 9 software. The result on this research is credit risk, operation risk, liquidity risk and capital adequacy have a negatif influence to profitability, and market risk with two variables, first inflation have a negatif influence and second BI rate have a positifinfluance to profitability. Second, syariah system has to reduce influence risk to profitability, they are eliminate credit risk and BI rate risk, and decrease risk impact to profitabilit in Bank Umum Swasta Nasional Devisa Indonesia. Keywords: credit risk, liquidity risk, operation risk, market risk and capital adequacy, profitability